Determinants Model in Reducing HIV-Related Stigma in Health care Workers: A Systematic Review - Handayani, Sri; Maidin, Alimin; Birawida, Agus Bintara; Suriah, Suriah; Ansariadi, Ansariadi; Indriasari, Rahayu; Stang, Stang (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: The stigma accepted by people living with HIV (PLWHA) is a major obstacle in HIV prevention, especially from health workers. Aims: This study aims to determine the factors associated with HIV stigma among health workers. Methods: This systematic review was conducted using the 2015 PRISMA guidelines. All publications by reading the title and abstract. In the final screening stage, the authors read the full text of the remainder of the article and held back studies that were consistent with inclusion criteria, focusing on HIV-related stigma determinants published in 2010-2020. Results: The stigma that comes from health workers to PLWHA can come from personal beliefs or a lack of personal confidence, which can be derived from self-confidence, self-confidence, knowledge, working time, and institutional support or policies from the workplace that create discriminatory behavior when dealing with PLWHA. The created stigma can reduce social interactions and the quality of life of PLWHA. Conclusion: It is important to find determinants to formulate appropriate intervention plans in reducing HIV-related stigma, especially among health workers.